PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2015 - Islami, Hafizh; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to examine persistently and simultaneously the influence of investment decisions, funding decisions, and dividend policy on firm value. Where the independent variables in this study are investment decisions, funding decisions, and dividend policies while the dependent variable is the value of the company. The sample used is secondary data derived from the financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2011 to 2015.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. Data analysis using multiple linear regression analysis, t test, F test, and determination coefficient test. Data analysis using multiple linear regression analysis with SPSS 24.The results of this study indicate that the variable investment decisions (t test) do not affect the value of the company, funding decision variables and dividend policy also do not affect the value of the company in the mining sector companies listed on the Indonesia Stock Exchange. Simultaneous test results (f) show no influence from investment decision variables, funding decisions and dividend policy on the value of the company in mining sector companies listed on the Indonesia Stock Exchange.Keywords : Investment decisions, funding decisions, dividend policies, and company values.